Práctica de enseñanza de lengua en educación general básica, análisis de caso en el primer año en la Escuela Juan Montalvo del Cantón Otavalo - Vargas Simba, Yesi Geovana (2016)
This research work was conducted at the Education Unit "Juan Montalvo" neighborhood Coast, Parish González Suárez, Canton Otavalo, this was carried out with the participation of teachers and children of the first year of Basic General Education, the institution. The procedure used to respond to the problem was the research as contact directly with reality in the classroom provided information on the context that exists in education, taking into account that early childhood is considered the fundamental stage in the life of human beings, where the development of skills and abilities is power. To do this when speaking of teaching practices Language, verbal and nonverbal communication in our social context the teaching and learning processes are directly linked with academic work of students and teachers. On teaching practices is not found information daily work of our teachers in the classroom, that motivated me to perform daily observation at the school. techniques and methods of scientific research that enabled us to collect, analyze and interpret results of the problem that exists within the institution was used for the preparation of certification work.